Protection of Children with Special Needs from Gender-Based Sexual Violence Through Family-Based Protection Programs - Yanti Lisnawati; Budi Susetyo; Iding Tarsidi; Ahsen Yılmaz; Muhammad Rijaal Qurrota A'yuni (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
Children with special needs, particularly girls with intellectual disabilities, are at high risk of experiencing gender-based sexual violence due to limitations in communication, understanding of risky situations, and dependence on adults. Despite increasing concerns regarding violence against children with disabilities, studies examining family-based protection integrated with special education interventions remain limited. This study aims to analyze the vulnerability and patterns of gender-based sexual violence experienced by children with intellectual disabilities and to examine the effectiveness of family-based protection programs through Special Programs (Progsus) and Reproductive and Sexual Health Education (PKRS). This study employed a descriptive qualitative approach using a case study design involving a 15-year-old girl with intellectual disabilities at State Special School 02 in Serang City, Indonesia. Informants included parents, teachers, and school personnel involved in the intervention process. Data were collected through gender-based violence assessments, in-depth interviews, observations, program documentation, and assistance records. Data were analyzed thematically using the interactive model of Miles, Huberman, and Saldaña, with triangulation employed to ensure trustworthiness. The findings revealed that the child experienced moderate levels of sexual violence perpetrated by individuals from her immediate environment. The implementation of Progsus and PKRS through school–family collaboration contributed to psychological recovery and improved self-protection skills, including the ability to recognize private body parts, distinguish safe and unsafe touch, and reject inappropriate treatment. Family involvement also enhanced parental awareness and responsiveness toward potential risks of sexual violence. This study highlights the strategic role of family-based protection programs integrated with adaptive sexuality education in preventing and addressing gender-based sexual violence among children with special needs. The findings provide practical implications for inclusive education policies and child protection programs that are sensitive to disability and gender issues.